Topological defects reveal the plasticity of glasses - Matteo Baggioli (Nature Communications, 2023)
Mixing theoretical topological structures with cutting-edge simulation methods, a recent study in Nature Communications has finally confirmed the existence of topological defects in glasses and their crucial role for plasticity.